(untitled) (Eurasian Research Bulletin, 2022)
This article deals with the study and linguistic bases of paraphrases in the English and Uzbek languages. Besides, the article includes the usage of paraphrases in speech, different viewpoints of scholars about paraphrases and the special features of phraseological compounds